(untitled) (Global Journal of Human-Social Science, 2019)
The Uyghurs in China remain under threat of assimilation, repression and discrimination, slowly becoming marginalised in their indigenous home-land. Uyghur Muslims, who constitute over 11 million of the Xinjiang Uyghur Autonomous Region (XUAR) population, are at the crossroads of victim-hood, deprivation and desire to rebuild their destiny. The Uyghur young minds not only hold high aspirations from their community leaders, but also have a strong desire to lead a respectable life and seek opportunities for progress and development similar to Han ethnicity communities. The Uyghur community at large is in a churning process, the condition of Uyghurs are generally worse than other ethnic races of China. The available research suggests Uyghur Muslims are lagging in all spheres of development including education, employment, income and assets. Deprivation amongst Uyghur Muslims exists due to a number of systematic factors. The marginalised Uyghur Muslim community should pursue social, economic and educational aspirations not only within the framework and with support of government provided infrastructure and opportunities, but also by talking the extra steps to achieve targets on their own.